2021
DOI: 10.1089/end.2020.1103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Patient-Specific Three-Dimensional Printing of Kidney Before Partial Nephrectomy: A Qualitative Assessment

Abstract: Objectives: To qualitatively assess the clinical usefulness of patient-specific high-fidelity three-dimensional (3D) print model of kidney before partial nephrectomy (PN) and to identify subset domains where it may help in clinical terms. Materials and Methods: Thirteen 3D models were printed for tumors having RENAL nephrometry score of ‡8. Their usage for PN was assessed prospectively using a qualitative questionnaire to be answered on a Likert scale of 1-10. The questions focused on realistic resemblance, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A randomized study 4 examining the use of 3DVR for surgical planning of RAPN found reductions in operative time (odds ratio [OR], 1.00; 95% CI, 0.37–2.70; estimated OR, 2.47), EBL (OR, 1.98; 95% CI, 1.04–3.78; estimated OR, 4.56), clamping time (OR, 1.60; 95% CI, 0.79–3.23; estimated OR, 11.22), and length of hospital stay (OR, 2.86; 95% CI, 1.59–5.14; estimated OR, 5.43). Furthermore, a report that assessed the usefulness of 3D models preoperatively and intraoperatively for difficult RAPNs with questionnaires rated 3D models higher than CT or ultrasound for surgical resection margin orientation 13 . These reports 4,13 indicate that 3DVRs and 3D models are effective in PN.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A randomized study 4 examining the use of 3DVR for surgical planning of RAPN found reductions in operative time (odds ratio [OR], 1.00; 95% CI, 0.37–2.70; estimated OR, 2.47), EBL (OR, 1.98; 95% CI, 1.04–3.78; estimated OR, 4.56), clamping time (OR, 1.60; 95% CI, 0.79–3.23; estimated OR, 11.22), and length of hospital stay (OR, 2.86; 95% CI, 1.59–5.14; estimated OR, 5.43). Furthermore, a report that assessed the usefulness of 3D models preoperatively and intraoperatively for difficult RAPNs with questionnaires rated 3D models higher than CT or ultrasound for surgical resection margin orientation 13 . These reports 4,13 indicate that 3DVRs and 3D models are effective in PN.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a report that assessed the usefulness of 3D models preoperatively and intraoperatively for difficult RAPNs with questionnaires rated 3D models higher than CT or ultrasound for surgical resection margin orientation. 13 These reports 4,13 indicate that 3DVRs and 3D models are effective in PN. However, they do not assess the extent to which the models were required, and there are no such reports in the literature.…”
Section: Discussionmentioning
confidence: 98%